The Use of Interactive LKPD to Improve Student Learning Outcomes in Science Learning Related to the Material of the Life Cycle of Living Things in Class III SDN Sangen 01 - Huwaidah, Yunita Nisrina; Sri Utami; Raden Syaifuddin (UNIVERSITAS PGRI MADIUN, 2024)
This research aims to determine the use of interactive LKPD in improving student learning outcomes in science learning with the topic of recognizing the cycles of living things in class III at SDN Sangen 01. This research uses the class action research (PTK) method. The number of students in this study was 8 class III students at SDN Sangen 01, consisting of 3 male students and 5 female students. This research was carried out in two cycles and began with pre-cycle actions. Each cycle is carried out with planning, implementation and reflection activities. Based on the results of this research, it shows that student learning outcomes in this pre-cycle action are still low with an average score of 60 and learning completeness of 37.5%. In the first cycle stage, it shows that student learning outcomes are quite good because there is an increase with an average score of 76 and learning completeness of 62.5%. Meanwhile, in the second cycle stage, data was obtained that student learning outcomes were higher than the previous cycle, with an average score of 83 and learning completeness of 87.5%. Students' responses to the use of interactive LKPD were initially from adequate to very feasible and the learning process was included in the good category. Based on this, the use of LKPD can improve student learning outcomes regarding material about the cycles of living things in class III at SDN Sangen 01.This research aims to determine the use of interactive LKPD in improving student learning outcomes in science learning with the topic of recognizing the cycles of living things in class III at SDN Sangen 01. This research uses the class action research (PTK) method. The number of students in this study was 8 class III students at SDN Sangen 01, consisting of 3 male students and 5 female students. This research was carried out in two cycles and began with pre-cycle actions. Each cycle is carried out with planning, implementation and reflection activities. Based on the results of this research, it shows that student learning outcomes in this pre-cycle action are still low with an average score of 60 and learning completeness of 37.5%. In the first cycle stage, it shows that student learning outcomes are quite good because there is an increase with an average score of 76 and learning completeness of 62.5%. Meanwhile, in the second cycle stage, data was obtained that student learning outcomes were higher than the previous cycle, with an average score of 83 and learning completeness of 87.5%. Students' responses to the use of interactive LKPD were initially from adequate to very feasible and the learning process was included in the good category. Based on this, the use of LKPD can improve student learning outcomes regarding material about the cycles of living things in class III at SDN Sangen 01.